Faktor-Faktor yang Mempengaruhi Literasi Keuangan Syariah pada Santri dengan Pendidikan Keuangan Keluarga sebagai Variabel Moderasi (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the effect of financial attitudes, socioeconomic status, gender, and education level on Islamic financial literacy with family finance education as a moderating variable (Empirical Study at As Salafy Al Asror Islamic Boarding School). The population in this study was the students of the As Salafy Islamic Boarding School Al Asror Patemon Gunungpati, Semarang City. The research sample was 213 Santri Pondok Pesantren As Salafy Al Asror which was determined by the sampling technique, namely purposive sampling. The data analysis method used is descriptive analysis, and inferential analysis. The results of the descriptive analysis showed that Islamic financial literacy, financial attitudes, socioeconomic status, and family financial education were in the medium category. The results of this study indicate that financial attitudes have a positive and significant influence on Islamic financial literacy. Socio-economic status and education level do not have a significant influence on Islamic financial literacy. Other results indicate that family financial education significantly moderates the effect of financial attitudes and social status on Islamic financial literacy. Family financial education does not significantly moderate the effect of education level on Islamic financial literacy.